2013
DOI: 10.1515/jpm-2013-0137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antenatal magnesium sulfate application on cord blood levels of brain-derived neurotrophic factor in premature infants

Abstract: The application of antenatal MgSO4 in preterm delivery increased cord blood BDNF levels, which could have a potential role on fetal neuroprotection. Further investigation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 8 publications
0
18
0
3
Order By: Relevance
“…The Alturas have recently demonstrated that short-term magnesium deficiency can down regulate telomerase [62] . In addition to this, Bachnas et al have shown that antenatal supplementation with magnesium sulfate in humans can improve the levels of BDNF [158] . In the setting of experimental menopause, Sandhir et al have found that coenzyme Q10 can ameliorate cognitive functions [159] .…”
Section: Discussionmentioning
confidence: 98%
“…The Alturas have recently demonstrated that short-term magnesium deficiency can down regulate telomerase [62] . In addition to this, Bachnas et al have shown that antenatal supplementation with magnesium sulfate in humans can improve the levels of BDNF [158] . In the setting of experimental menopause, Sandhir et al have found that coenzyme Q10 can ameliorate cognitive functions [159] .…”
Section: Discussionmentioning
confidence: 98%
“…Magnesium's anti‐inflammatory properties are also observed in vitro in cord blood mononuclear cells of the human neonate . The rate of brain‐derived neurotrophic factor production is correspondingly elevated in the cord blood of infants born preterm whose mothers received magnesium sulphate, which is consistent with an anti‐inflammatory effect . In a murine model of perinatal neuroinflammation, long‐term sex‐specific benefits were observed in magnesium sulphate/betamethasone‐treated cases relative to a placebo group.…”
Section: Mechanisms Involved In the Neuroprotective Effects Of Magnesmentioning
confidence: 76%
“…16 The rate of brain-derived neurotrophic factor production is correspondingly elevated in the cord blood of infants born preterm whose mothers received magnesium sulphate, which is consistent with an anti-inflammatory effect. 17 In a murine model of perinatal neuroinflammation, long-term sex-specific benefits were observed in magnesium sulphate/betamethasone-treated cases relative to a placebo group. The sex-specific effect favoured males; a minimal injury causing a greater alteration to gene control among females, or a heightened susceptibility to magnesium or betamethasone among males, may account for the sex-specific discrepancy.…”
Section: Mechanisms Involved In the Neuroprotective Effects Of Magnesmentioning
confidence: 99%
“…This theory is supported by several recent papers that demonstrate a suppression of cord blood cytokine production with MgSO 4 use . In 2014, a randomised controlled trial in 72 women showed increased levels of brain‐derived neurotrophic factor (BDNF) in cord blood of preterm babies (born before 34 weeks of gestation) where MgSO 4 (4 g loading dose and 1 g/h until delivery) had been given antenatally, compared with placebo . BDNF is a neurotrophin shown to be protective against neonatal hypoxic‐ischaemic brain injury in vivo .…”
Section: Proposed Mechanism Of Action Of Magnesium Sulfate (Mgso4) Fomentioning
confidence: 90%